Agro-climatic regionalization of kernel apricot (prunus armeniaca × sibirica) plantations in beijing - Li , Ling; Gao, Zhaoquan (Bangladesh Journal of Botany, 2024)
This study envisaged the distribution of the kernel apricot producing areas in Beijing using GIS technology, based on the climatic and geographical data of Beijing. The kernel apricot cultivation areas in Beijing area were classified as the most suitable area, suitable area, general suitable area, unsuitable area and least suitable area. The results indicated that the plains, hills, shallow mountains and valley basins of Beijing were the most suitable distribution areas of kernel apricot. The main cultivation places were in mountainous areas and shallow mountainous areas, and were classified under the suitable areas and general suitable areas of kernel apricot cultivation. At present, the planting area of kernel apricot in Beijing was 8346 hectares, which is the third largest economic forest tree species. It was found that the main production areas of kernel apricot included the Yanqing producing areas, western mountain producing areas and the northern mountain producing areas, accounting for more than four fifths of the cultivated area of kernel apricot in the city. Bangladesh J. Bot. 53(4): 1067-1075, 2024 (December)